PENGEMBANGAN LEMBAR KEGIATAN PESERTA DIDIK (LKPD) BERBASIS PENDEKATAN SETS (SCIENCE, ENVIRONMENT, TECHNOLOGY AND SOCIETY) PADA MATA PELAJARAN KIMIA SMA/MA POKOK BAHASAN KESETIMBANGAN KIMIA - Fitra Fadliani; Susilawati Susilawati; Rasmiwetti Rasmewetti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The aim of this research is to develop a Student Worksheet (SWs) based on the SETS (Science, Environment, Technology and Society) Approach on the subject of Chemical Equilibrium. This type of research is research and development (R & D) with ADDIE development models which include Analysis, Design, Development, Implementation and Evaluation. This research was carried out to the Implementation stage in the form of limited trials to teachers and students. This research was conducted at FKIP Riau University, Babussalam Pekanbaru High School and MAN 2 Pekanbaru. The object of this research is the SWs based on the SETS approach. The data analysis technique used in this study is descriptive statistical analysis, carried out by calculating the score obtained at the time of validation. The assessment of the feasibility aspects of SWs by the validator team in the form of content eligibility, characteristics of the SETS approach, linguistic, presentation, and graphic characteristics respectively scored 93.05%, 95.00%, 91.66%, 95.84%, and 91, 66%. So, overall the average score of the chemical equilibrium SWs based on the SETS approach is 93.44% included in the valid eligibility criteria, meaning that the developed Sws is eligible to be tested on a limited basis whereas the response of teachers and students towards SWs gets a percentage of 94.64% and 84.82% are in good criteria.  Key Words: Student WorkSheet (SWs), SETS Approach, and Chemical Equilibrium